APPLICATION OF THE TEAM GAMES TOURNAMENT (TGT) COOPERATIVE LEARNING MODEL IN IMPROVING CIVICS LEARNING RESULTS - Galih Pandu Wiratama (Academic Solution Publisher, 2024)
Current learning activities demand that teachers can meet the learning needs of students and provide stimulation for the development of students' unique potential, including their talents, interests and creativity, so choosing suitable learning methods will have a positive impact on improving the quality of students' learning. At SMP Negeri 6 Medan, the main problem experienced is the decline in Civics learning outcomes of students in class 7-B. One of the efforts taken to improve it is by implementing a cooperative learning model with the Teams Games Tournament (TGT) model in Civics learning in the classroom. This study aims to determine the effect of the TGT type cooperative learning model which is a solution in making improvements in learning outcomes. The research method used is Classroom Action Research (PTK) using a qualitative approach. Data from learning outcomes and student participation after the implementation of the TGT model. Thus, it can be concluded that the Teams Games Tournament (TGT) cooperative learning approach succeeded in providing an increase in learning outcomes and student learning involvement in Civics subjects in the classroom.